Meningkatkan Prestasi Belajar Siswa dengan Menerapkan Metode Model Jigsaw Siswa kelas II Sekolah Dasar - Hj Karliati (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2020)
The purpose of this study was to improve student learning achievement by applying the Jigsaw Model Method for Class II Semester II students of Public Elementary School 04 Pao, Tanete Rilau District, Baru Regency, 2016/2017 Academic Year. This research was conducted in Class IV SDN No. 04 Paodengan implementation stages include (1) Planning, (2) Implementation, (3) Observation and evaluation, (4) reflection. The results of the analysis of this study obtained an overview of the test results in cycle 1 (one) of learning by applying the jigsaw model not yet showing maximum results. This shows that the results of the first cycle test were 62.88%, while the second cycle test results showed a satisfactory result of 74.62%. Whereas the cycle has shown good learning outcomes with test results of 83.46%. These results indicate that applying the jigsaw model in thematic learning of grade II SDN Pao students can improve student achievement.